Migration of Legacy Mumps Applications to Relational Database Servers - O’Kane, K. C. (Methods of Information in Medicine, 2001)
An extended implementation of the Mumps language is described that facilitates vendor neutral migration of legacy Mumps applications to SQL-based relational database servers. Implemented as a compiler, this system translates Mumps programs to operating system independent, standard C code for subsequent compilation to fully stand-alone, binary executables. Added built-in functions and support modules extend the native hierarchical Mumps database with access to industry standard, networked, relational database management servers (RDBMS) thus freeing Mumps applications from dependence upon vendor specific, proprietary, unstandardized database models. Unlike Mumps systems that have added captive, proprietary RDMBS access, the programs generated by this development environment can be used with any RDBMS system that supports common network access protocols. Additional features include a built-in web server interface and the ability to interoperate directly with programs and functions written in other languages.
Keywords: Mumps; SQL; Patient Records; Relational Database Server